Upaya Peningkatan Keterampilan Membaca Di Kelas Tinggi - Arwita Putri; Riris Nurkholidah Rambe; Intan Nuraini; Lilis Lilis; Pinta Rojulani Lubis; Rahmi Wirdayani (Pusat Riset dan Inovasi Nasional, 2023)
Reading is the ability to use thoughts and actions to perform visual activities, pronounce a series of letters into words and sentences, master reading techniques and understand the content of the reading correctly. The method used in this study is a literature analysis study. Reading skills are skills that focus on reading words and sentences. The aspects in reading, it seems like pronunciation accuracy, intonation, fluency, clarity of voice and reading ability intact. Reading skills are the ability for a person to be able to read a reading properly and correctly, and can get the message contained in the reading. The purpose of reading is to find and obtain information, include its content and understand the meaning of reading.